The Relationship Between the Quality of Health Services and the Level of Satisfaction of Outpatients District - Sumiati, Sumiati; Nanda, Meutia; Susanti, Nofi (Indonesian Journal of Global Health Research, 2024)
Service quality is to provide patient services at the Bandar Khalifah Health Center so that what is provided and pasein satisfaction is a patient's satisfaction and comfort to get more patients. Patient satisfaction is one of the important indicators that must be considered in health services at the Bandar Khalifah Health Center. The number of patient visits at the Bandar Khalifah Health Center, percut sei tuan district, deli serdang.2020 as many as 13,654 people, and in 2023 as many as 17,594 people.The purpose of this study was to determine the relationship between the quality of health services and the level of satisfaction of outpatients at the Bandar Khalifah Health Center, Percut Sei Tuan District, Deli Serdang. This type of research is quantitative with a cross sectional approach. This data collection uses a questionnaire. Data analysis using univariate and bivariate analysis with the Chi-Square test. The population in this study were outpatients totaling 368 in February 2024. The sample in this study amounted to 55 people. The results of this study indicate a relationship between the quality of health services and the level of Outpatient Patient Satisfaction with a value of p = 0.00. (p-value ≤0.05). Reliability with outpatient patient satisfaction with a p value = 0.00 (p-value ≤0.05). Responsiveness with Patient Satisfaction.